Penerapan Simulasi Debat untuk Meningkatkan Kemampuan Berargumentasi Peserta Didik pada Pembelajaran Pendidikan Pancasila Kelas XI di SMAN 7 Surabaya - Prima Adi Kurniawan (Universitas Negeri Surabaya (Unesa), 2026)
This study aims to improve students' argumentation skills through the application of the debate simulation method in Pancasila Education classes for grade XI-B at SMAN 7 Surabaya. The study used a classroom action research approach with Kemmis & McTaggart's reflective spiral model, which was implemented in three cycles over two months. The research subjects were 30-35 students in class XI-B, with data collected through participatory observation, in-depth interviews, and documentation. The data were analyzed using the interactive analysis method of Miles and Huberman. The results showed that the application of the debate simulation method successfully improved students' argumentation skills significantly. In Cycle I, students adapted to the debate method and began to show the courage to express their opinions. In Cycle II, using a simple argument structure worksheet, students were able to construct a more coherent argumentation logic. In Cycle III, students had achieved a comprehensive level of argumentation, based on data and accompanied by objective rebuttals. In addition to improving argumentation skills, this method also developed 21st-century competencies, increased self-confidence, fostered democratic attitudes, and trained students in collaboration.